1980
DOI: 10.1159/000123094
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Kinetics of Dopamine Uptake in Synaptosome Preparations of the Median Eminence Relative to Other Dopaminergically Inervated Brain Regions

Abstract: A comparison of the kinetics of dopamine uptake was made in synaptosomal preparations of the median eminence, striatum and olfactory tubercle. Double reciprocal Lineweaver-Burk plots of the initial velocity versus the concentration of dopamine yielded a single straight line in all three areas. The Michaelis constant (Km) in the median eminence (1.8 ± 0.9 × 10–6M) was significantly higher (p<0.05) than in the striatum (4.2 ± 0.8 × 10–8M) or olfactory tubercle (6.3 ± 1.9 × 10 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(31 citation statements)
references
References 20 publications
6
24
1
Order By: Relevance
“…In the SME, we observed an increase in the D A content during long days while DOPAC, the first metabolite, was poorly represented and showed no statistically significant differences between groups. The same was observed previously ( I I), and the failure to reach significance in both studies could be the consequence of too low a content of the metabolite due to the relative ineffectiveness of the re-uptake mechanism of the TIDA system, as demonstrated in the rat (17,18). In ram lambs (1 I), the increased dopaminergic activity associated with lower gonadotrophin-releasing hormone secretion was due to the negative feedback effect of steroids, while in our experiments, most changes in catecholamines were essentially due to modifications in L H secretion in relation to daylength.…”
Section: Discussionsupporting
confidence: 85%
“…In the SME, we observed an increase in the D A content during long days while DOPAC, the first metabolite, was poorly represented and showed no statistically significant differences between groups. The same was observed previously ( I I), and the failure to reach significance in both studies could be the consequence of too low a content of the metabolite due to the relative ineffectiveness of the re-uptake mechanism of the TIDA system, as demonstrated in the rat (17,18). In ram lambs (1 I), the increased dopaminergic activity associated with lower gonadotrophin-releasing hormone secretion was due to the negative feedback effect of steroids, while in our experiments, most changes in catecholamines were essentially due to modifications in L H secretion in relation to daylength.…”
Section: Discussionsupporting
confidence: 85%
“…The Michaelis-Menten constant for DA uptake calcu lated from Lineweaver-Burk plots for the NIL (2.2x 1 0 * /V/) was similar to that observed in the median emi- nence (1.8 x 10 6 M), another terminal region of the tuberoinfundibular dopaminergic system [1], The Km values for these two areas differ notably from the nigrostriatal and mesolimbic dopaminergic systems [17.26, 28], In the striatum and olfactory tubercle the K",sfor 'H-DA uptake ranged from 4 to 5 x while in the neurointer mediate lobe and median eminence [1] the values were ap proximately 25 times higher.…”
Section: Discussionsupporting
confidence: 69%
“…It is known that the kinetics of dopamine uptake in the terminals of the tuberoinfundibular neurons markedly differ from those of the nigrostriatal and mesolimbic systems (103). In situ and Northern hyblidization has shown that hypothalamic neurons display much less DAT mRNA than that found in nigra compacta neurons (47).…”
Section: Permeation Pathwaymentioning
confidence: 99%